2022
DOI: 10.1002/casp.2632
|View full text |Cite
|
Sign up to set email alerts
|

Fighting inequalities in times of pandemic: The role of politicized identities and interdependent self‐construal in coping with economic threat

Abstract: During the COVID-19 pandemic, institutions encouraged social isolation and non-interaction with other people to prevent contagion. Still, the response to an impending economic crisis must be through the collective organization. In this set of pre-registered studies, we analyse two possible mechanisms of coping with collective economic threats: shared social identity and interdependent self-construction. We conducted three correlational studies during the pandemic in May-October 2020 (Study 1, N = 363; Study 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Not only competition but other variables that reflect social and psychological distance/cohesion may be considered when studying economic inequality, such as self-construal (Sánchez-Rodríguez et al, 2019). Indeed, recent studies have shown that self-construal explains the effect of economic threat on different psychosocial outcomes (Del Fresno-Díaz et al, 2022). A second limitation of our studies is the lack of the assessment of participants' political orientation.…”
Section: Discussionmentioning
confidence: 96%
“…Not only competition but other variables that reflect social and psychological distance/cohesion may be considered when studying economic inequality, such as self-construal (Sánchez-Rodríguez et al, 2019). Indeed, recent studies have shown that self-construal explains the effect of economic threat on different psychosocial outcomes (Del Fresno-Díaz et al, 2022). A second limitation of our studies is the lack of the assessment of participants' political orientation.…”
Section: Discussionmentioning
confidence: 96%
“…Desde esta perspectiva, la identidad colectiva se politiza desde el momento en que las personas "interpretan la posición del endogrupo y exogrupos, y las relaciones entre ellos, atendiendo a ese contexto más amplio" (Sabucedo et al, 2010, p. 194). En este sentido, ante la amenaza de la COVID-19 las relaciones de poder según la filiación política y el posicionamiento ideológico dieron lugar a procesos de identidad colectiva politizada (Fresno-Díaz et al, 2020). Esta relación entre el espectro ideológico y las distintas medidas asociadas a la justificación ha sido ampliamente estudiada (Sterling et al, 2020).…”
Section: Enmarcamiento Y Configuración Una Identidad Colectiva Politi...unclassified
“…del Fresno-Díaz et al (2023) examine mechanisms that drive collective action around economic threats during the COVID-19 pandemic, when encouraged social isolation may have impeded such action. With samples of Spanish adults, they document that shared identity (working-class and 99% identity), and interdependent self-construal served as mediators between collective economic threat and intolerance to such threats and desires to engage in collective action to address economic threats.…”
Section: Collective Action and Challenging Inequalitymentioning
confidence: 99%